Conceptualizing Johnson's typology of intimate partner violence in queer relationships - Bermea, Autumn M. (Journal of family violence, 2024)
Purpose: Johnson’s (2008) typology revolutionized how intimate partner violence (IPV) was conceptualized. Broadly, it distinguished different ways that IPV manifested and motivations for perpetrating IPV. Contemporary queer theorists and researchers have critiqued the typology as being too cis-heteronormative, or assuming cisgender identity and heterosexuality as default identities and experiences. Our purpose then is to make visible the unintended cis-heteronormativity in Johnson’s typology of IPV and articulate ways to enhance its use with queer populations. Method: We used queer theory to reconceptualize cis-heteronormative tenants of Johnson’s (2008) typology and propose a more inclusive understanding of IPV. We also used queer of color critique to consider additional intersectional locations (e.g., race) that can lead to relational power imbalances. Results: We developed two queer theoretical extensions to Johnson’s (2008) typology that are reflective of the dynamics of diversity in queer relationships. In them, we engage in Challenging Categorization through Contextualizing Prevalence Estimates of IPV Among Queer US Populations and (Re)Conceptualizing Categorization (Extension 1). We also engage in (Re)Conceptualizing Power and Control (Extension 2). Conclusion: Our theoretical extensions can be used to advance the field of IPV research in ways that are inclusive of queer peoples’ experiences of IPV.